Corn Cost-Return Budget in Northeast Kansas - Lubben, Bradley D.; Staggenborg, Scott A. (My University, 2001)
This publication projects a budget that reflects expected income and costs based on typical corn production practices in northeastern Kansas.
MF571_2001_10
Keywords: MF571; Economics; Crops; MF